Nonlinear Optical Crystals with Asymmetric Electron Donating Groups for Efficient Terahertz Wave Generation - 이채원 (The Graduate School, Ajou University, 2024)
In the realm of organic nonlinear optical materials for terahertz (THz) generation, achieving a delicate balance between large optical nonlinearity and minimal molecular vibration is crucial. Additionally, maintaining a noncentrosymmetric molecular ordering in the crystalline state is essential for second-order optical nonlinearity. However, the challenge arises from the high dipole moment of organic π-conjugated chromophores, often leading to a centrosymmetric ordering in the crystalline state. This study focuses on the development of asymmetric electron- donating group (EDG)-based crystals, addressing the need for large optical nonlinearity, low molecular vibration, and noncentrosymmetric alignment. The molecular engineering involves three components: donor, anion, and acceptor, derived from the mother crystal PB-7ClQ-CBS. The donor part introduces a novel EDG, extending the asymmetric five-membered ring to a six-membered ring, where (S)-4-(2-(hydroxymethyl)pyrrolidinyl)benzaldehyde (PB) outperforms 4-(3- (hydroxymethyl)piperidinyl)benzaldehyde in terms of low molecular vibration, planar crystal structure, and noncentrosymmetric alignment. The introduction of halogen-substituted benzenesulfonate anions, particularly (S,E)-7-chloro-2-(4-(2- (hydroxymethyl)pyrrolidinyl)styryl)methylquinolinium 4-bromobenzenesulfonate, enhances isomorphism with the mother crystal, resulting in lower void volume and higher density conducive to reduced molecular vibration. Finally, the PB-5FB-T crystal, incorporating the strong electron-withdrawing group benzothiazolium as the acceptor, exhibits substantial macroscopic optical nonlinearity, perfect in-plane orientation, and low molecular vibration. Notably, the THz electric field amplitude surpasses that of the benchmark ZnTe crystal. In conclusion, asymmetric EDG PB- based crystals demonstrate the potential for high efficiency in THz wave generation, offering promising prospects in the field.
학위논문(석사)--분자과학기술학과,2024. 2
Keywords: Nonlinear optical crystal; Terahertz